2022
DOI: 10.1111/pde.15209
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric pulse dose corticosteroid therapy dosing and administration in the treatment of alopecia areata: A review of literature

Abstract: Background The use of pulse dose corticosteroid therapy (PDCT) in children for treatment of alopecia areata (AA) has been reported, but dosing regimens are not well‐established. We aim to evaluate the available literature regarding the utilization and various dosing regimens of PDCT, as well as associated side effects, in the treatment of AA in children. Methods We performed a systematic review of studies describing the use of PDCT for the treatment of AA in children. Results Eight relevant studies were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Furthermore, corticosteroids are used as a treatment in AA [ 93 , 94 , 95 ]. Topical corticosteroids and pulse dose corticosteroid therapy also show effectiveness in pediatric AA [ 96 , 97 ].…”
Section: Acth Crh and Cortisolmentioning
confidence: 99%
“…Furthermore, corticosteroids are used as a treatment in AA [ 93 , 94 , 95 ]. Topical corticosteroids and pulse dose corticosteroid therapy also show effectiveness in pediatric AA [ 96 , 97 ].…”
Section: Acth Crh and Cortisolmentioning
confidence: 99%
“…Systemic corticosteroids are reserved for more extensive or rapidly progressing AA due to their potential side effects and are used cautiously in pediatric cases. A recent analysis encompassing eight studies and involving 216 children found that 56% experienced more than 50% hair regrowth on their scalp after undergoing treatment with pulse systemic steroids [6]. Several investigations have focused on pediatric patients undergoing methotrexate therapy.…”
Section: Andandmentioning
confidence: 99%
“…In a subsequent pediatric review of 8 studies (216 children), 56% reported >50% regrowth of scalp hair. 64 …”
Section: Corticosteroidsmentioning
confidence: 99%